Lymphocytes and macrophages in adipose tissue in obesity: markers or makers of subclinical inflammation? - Cinkajzlová, Anna; Mráz, Miloš; Haluzík, Martin (Protoplasma, 2017)
Obesity is accompanied by the development of chronic low-grade inflammation in adipose tissue. The presence of chronic inflammatory response along with metabolically harmful factors released by adipose tissue into the circulation is associated with several metabolic complications of obesity such as type 2 diabetes mellitus or accelerated atherosclerosis. The present review is focused on macrophages and lymphocytes and their possible role in low-grade inflammation in fat. Both macrophages and lymphocytes respond to obesity-induced adipocyte hypertrophy by their migration into adipose tissue. After activation and differentiation, they contribute to the development of local inflammatory response and modulation of endocrine function of adipose tissue. Despite intensive research, the exact role of lymphocytes and macrophages within adipose tissue is only partially clarified and various data obtained by different approaches bring ambiguous information with respect to their polarization and cytokine production. Compared to immunocompetent cells, the role of adipocytes in the obesity-related adipose tissue inflammation is often underestimated despite their abundant production of factors with immunomodulatory actions such as cytokines or adipokines such as leptin, adiponektin, and others. In summary, conflicting evidence together with only partial correlation of in vitro findings with true in vivo situation due to great heterogeneity and molecular complexity of tissue environment calls for intensive research in this rapidly evolving and important area.
Keywords: Adipocytes; T-lymfocyty pomocné-indukující; Inflammation; Obesity; Lymphocytes; cytokiny; zánět; Diabetes Mellitus, Type 2; Adipokines; Low-grade inflammation; Mice; Cytokines; diabetes mellitus 2. typu; Macrophages; zvířata; Humans; adipokiny; biologické markery; Adipose Tissue; myši; makrofágy; obezita; Biomarkers; T-Lymphocytes, Helper-Inducer; tuková tkáň; lidé; Animals